ASN1‐encoded asparagine synthetase in floral organs contributes to nitrogen filling in Arabidopsis seeds. (23rd May 2017) - Gaufichon, Laure; Marmagne, Anne; Belcram, Katia; Yoneyama, Tadakatsu; Sakakibara, Yukiko; Hase, Toshiharu; Grandjean, Olivier; Clément, Gilles; Citerne, Sylvie; Boutet‐Mercey, Stéphanie; Masclaux‐Daubresse, Céline; Chardon, Fabien; et al.
Summary: Despite a general view that asparagine synthetase generates asparagine as an amino acid for long‐distance transport of nitrogen to sink organs, its role in nitrogen metabolic pathways in floral organs during seed nitrogen filling has remained undefined. We demonstrate that the onset of pollination in Arabidopsis induces selected genes for asparagine metabolism, namely ASN1 ( At3g47340 ), GLN2 ( At5g35630 ), GLU1 ( At5g04140 ), AapAT2 ( At5g19950 ), ASPGA1 ( At5g08100 ) and ASPGB1 ( At3g16150 ), particularly at the ovule stage (stage 0), accompanied by enhanced asparagine synthetase protein, asparagine and total amino acids. Immunolocalization confined asparagine synthetase to the vascular cells of the silique cell wall and septum, but also to the outer and inner seed integuments, demonstrating the post‐phloem transport of asparagine in these cells to developing embryos. In the asn1 mutant, aberrant embryo cell divisions in upper suspensor cell layers from globular to heart stages assign a role for nitrogen in differentiating embryos within the ovary. Induction of asparagine metabolic genes by light/dark and nitrate supports fine shifts of nitrogen metabolic pathways. In transgenic Arabidopsis expressing promoter Ca MV 35S :: ASN1 fusion, marked metabolomics changes at stage 0, including a several‐fold increase in free asparagine, are correlated to enhanced seed nitrogen. However, specific promoter Napin2S :: ASN1 expression during seed formation and a six‐fold increase in asparagine toward the desiccation stage result in wild‐type seed nitrogen, underlining that delayed accumulation of asparagine impairs the timing of its use by releasing amide and amino nitrogen. Transcript and metabolite profiles in floral organs match the carbon and nitrogen partitioning to generate energy via the tricarboxylic acid cycle, GABA shunt and phosphorylated serine synthetic pathway. Significance Statement: Physiological role of asparagine during the period of embryogenesis in floral organs is investigated by modifying timing of asparagine synthesis. Onset of pollination promotes amino acid metabolism in photo‐heterotrophic floral organs at the expense of the amide‐ and amino‐groups of asparagine for nitrogen filling into seeds.